PENGARUH KEBIJAKAN PEMEKARAN WILAYAH KECAMATAN TERHADAP TINGKAT KESEJAHTRAAN MASYARAKAT (Suatu Studi Di Kecamatan Bunaken Kota Manado) - ARUNDE, IRENE; MANDEY, JANTJE; DENGO, SALMIN (JURNAL ADMINISTRASI PUBLIK, 2014)
Abstract: The foreigh to enlarge a district as a movement to increase the ability of the district governmentto make a short control of the government and to increase the human prosperity. As a matter of fact thereare still found the people in the districk has unprosperty. Based on the fact, so this research has to intendto answer the question, â€œwhether the enlarge of districk effective to the level of human prosperityâ€.The research used the quantitative method. This research is made based on five example areas in thedistrict Bunaken of Manado city, The research sampel is stated for one-hundred respondens which istaken twenty sampel of the respondens for dach area in the district randomly, to collect the data thequestioner methad is used and helping by the interview technique. The data analysis used statistic analysisregression linear and correlation product moment.Based the data analysis show that : The effectiveness coefficient regression of the foreigh to enlarge adistrict area concerning human properity is 0.779 scale for each unit, and Coefficient collation effect in theforeigh to enlarge a district area concerning human prosperity is 0,83, and the determination coefficient is0,69 or 69%. Based of the research, the conclusion is the foreigh to enlarge the district area has a positiveeffect and significant to improve the human prosperity.Based of the coclusion above, suggesting forresponsive of the government to running this program to create the human prosperity.Keywords : The foreigh to enlarge a district, prosperity.